Shy Plumber, Anti-War Journal of Art and Anti-Art : Issue III - Orlov, Ilya; Cowan, Matthew; Ustinov, Andrey (Shy Plumber Press, 2022)
Shy Plumber (ISSN 2736-8203) is an independent international art periodical published in Helsinki. Invented in 2020, the journal is focused on conceptual art today in its varied forms. It publishes artworks, considering them a fully-fledged analogue of showing it at a gallery or museum exhibition, as well as texts in art theory, intentionally and programmatically blurring the borders between art and philosophy, word and image, practice and theory. The editors are Ilya Orlov (Helsinki), Matthew Cowan (Berlin), Andrey Ustinov (Berlin). Issue III of Shy Plumber, Anti-War Journal of Art and Anti-Art published 8.8.2022 in Helsinki presents over twenty Finnish and international artists and writers. With Issue III - the third by number and the first after the Russian criminal military invasion of Ukraine began - the journal unequivocally takes solidarity with Ukraine and changes its name from ‘Shy Plumber, a Journal on Art and Anti-Art’ to ‘Shy Plumber, ANTI-WAR Journal of Art and Anti-Art’.
Keywords: taiteellinen tutkimus; taidefilosofia; kuvataide; taideteokset